2017
DOI: 10.3390/w9020133
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying River Channel Stability at the Basin Scale

Abstract: This paper examines the feasibility of a basin-scale scheme for characterising and quantifying river reaches in terms of their geomorphological stability status and potential for morphological adjustment based on auditing stream energy. A River Energy Audit Scheme (REAS) is explored, which involves integrating stream power with flow duration to investigate the downstream distribution of Annual Geomorphic Energy (AGE). This measure represents the average annual energy available with which to perform geomorpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 176 publications
(190 reference statements)
0
38
0
Order By: Relevance
“…Furthermore, even at the catchment scale, it is not economically and practically feasible to measure along the total length of a number of streams, especially considering that changing inputs of water, sediment, and vegetation often lead to alterations of river morphology over short time scales. In particular, moderate annual peak floods lead to altered cross‐sectional geometry while rare infrequent events cause significant channel change (Buffington, ; Soar et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, even at the catchment scale, it is not economically and practically feasible to measure along the total length of a number of streams, especially considering that changing inputs of water, sediment, and vegetation often lead to alterations of river morphology over short time scales. In particular, moderate annual peak floods lead to altered cross‐sectional geometry while rare infrequent events cause significant channel change (Buffington, ; Soar et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Most chemical approaches, based on chemical measurements, could detect specific types of degradation only associated with chemical sources like eutrophication of nitrogen and phosphorus or organic or inorganic toxicants, but did not reflect the habitat alterations of stream environments or biological health [8][9]. For these reasons, integrated approaches using biological, chemical, and physical parameters were required for efficient stream health monitoring and management [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This thinking has been extended by the suggestion that channel network surveys can enable channel characteristics and adjustments to be considered as part of a more holistic, catchment‐based approach: River styles have been advocated for catchment characterization with implications for river rehabilitation in the Bega catchment, NSW, Australia (Brierley & Fryirs, ), and in Dumaresq Creek, NSW, Australia, a method of field survey could complement the existing stormwater management plan (Gregory, ). A basin‐scale study for characterizing and quantifying river reaches in terms of their geomorphological stability status and potential for morphological adjustment based on auditing stream energy suggested that emerging geographic information system tools offer the future prospect of fully quantifying river channel stability at the basin scale (Soar, Wallerstein, & Thorne, ). Particularly in urbanizing areas, the common approach to treat the symptoms by modifying and stabilizing the channel may, after channel network survey, be succeeded by a holistic, catchment‐based approach (Vietz, Walsh, & Fletcher, ).…”
Section: Sequence Of Research Stagesmentioning
confidence: 99%